(untitled) (14th CONSTRUCTAL LAW CONFERENCE | 10-11 October 2024, Bucharest, Romania, 2024)
Throughout history, humanity has passed through many periods, and new builds are designed in every step. The new construction builds and environments have changed their habits and habitats. Nowadays, nature requires explanations about old historic buildings and their structural systems. According to the study’s latest design criteria, new structural and earthquake design models were implemented to provide the internal structures and contribute to constructional cost analysis. The regulations require natural designs, sustainable systems, and functionality, among other daily needs. Humanity has recently lost and ruined all architectural designs, disciplines, laws, and engineering criteria. Thus, humanity has tried to provide balance, find a definite solution, and create natural designs. The study discovered new criteria, models, methods, calculation ways, and explanations about life in the world. Furthermore, many ecological investments are made, and people try to support them, especially engineers, architects, and economists, who invest in natural energy. Therefore, the studies show a positive way that it can be applied in all regions worldwide, which is most effective. They contain the sustainable architecture and engineering criteria and assume the additional requirements. You can see more details below.